Water dams for use in drip irrigation in the city of penedo / Al: physico-chemical and biological quality - Oliveira Silva, Orlando; dos Santos, Elane Cristina Lourenço; Lopez, Ana Maria Queijeiro (Eclética Química, 2014)
In areas where rainfall is irregular or not reaches the required the supply for cane cultivation, irrigation is essential. The introduction of drip irrigation (with surface or underground micro-sprinklers), has been one of the factors that contributed to the increase in sugar and alcohol productivity in the region of Alagoas. This study outlined a profile of physico-chemical and biological features of impounded water dam “Salvador Lyra”, in the city of Penedo-AL, used to irrigate crops in a sugarcane mill, with the purpose to know the causes of obstructions detected in the issuing of the drip irrigation system, and to propose consistent control measures. During the period of one year, samples from three points along the dam were subjected to microbiological analysis and pH, hardness, electrical conductivity, concentraction of total dissolved solids, dissolved oxygen and Fe2. With respect to microbiological analysis, it was isolated from the neutral waters an aerobic bacteria producing siderophore iron chelators, classified as the species Pseudomonas aeruginosa (Schroeter 1872) Migula (1900), and the results of physico-chemical analysis showed the prevalence of with a high risk of biological clogging (> 50,000 cells / mL).